Gender Relation Patterns of Women’s Activities in the Production Process of Radio Broadcast Programs in Kediri City - Siti Amanah; Retpitasari, Ellyda; Hakim, Lukman (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
This research describes and analyzes the pattern of gender relations of women’s activities in the production process of radio broadcast programs on Andika FM and Bonansa FM radio in Kediri City and the factors that influence women’s access and control in the production process of radio broadcast programs. This research uses a descriptive qualitative approach in which the data collection techniques include observation, in-depth interviews, and documentation. The data analysis method utilized is gender analysis, known as the Harvard gender analysis method, or Gender Framework Analysis (GFA). Based on the study results, it can be concluded that women are actively involved in various radio activities at Andika FM and Bonansa FM. Women’s activities in multiple roles encourage changes in gender relations at the local cultural level, from the subordinate position of women to a more equal relationship. Women’s activities in the radio world have reached the stage of providing broad access for women to manage the radio, design and determine broadcast content, and produce radio programs. Factors influencing women’s access and control in the production process of radio programs at Andika FM and Bonansa FM radio include education level, company leadership policies, and awareness of gender equality between men and women.